Parents' accounts of the presence of their preadolescent child during discussions with doctors in the months after the child's diagnosis with serious illness: qualitative interview study. (29th September 2015) - Young, B; Ward, J; Salmon, P; Gravenhorst, K; Hill, J; Eden, T
Abstract : Aims: To examine parents' views regarding their child's presence during consultations. Method: Qualitative interview study using maximum variation sampling to recruit 66 parents (39 mothers, 27 fathers) of 42 children aged 1–12 years (median 4 years). Children were receiving treatment for acute lymphoblastic leukaemia at 6 UK paediatric oncology tertiary centres. The constant comparative method of analysis was used. Results: Parents acknowledged the benefits of communicating openly with children, but only five of the 53 parents who spoke on this issue thought their child's presence in consultations was automatically desirable. Parents described how their child's presence restricted their own communication with doctors, made it difficult for them to concentrate on what was said and interfered with their efforts to help their child feel safe and hopeful. The child's presence was particularly difficult for parents when "significant" issues were discussed. These issues included the prognosis, adverse test results and even routine medical procedures. Parents felt such discussions were a potential threat to their child, particularly when they had not had an opportunity to first discuss the information with doctors separately from their child, whereas separate discussions enabled parents to absorb the information themselves and to sanction its communication to their child. Some parents experienced difficulties in accessing separate consultations with doctors. Conclusions: The difficulties we identify are unlikely to be satisfactorily resolved by either systematically excluding children from consultations or the reverse. However, these difficulties could potentially be addressed by extending, beyond the diagnosis period, the practice of sequencing "significant" information so that it is first communicated to parents in separate consultations, and by periodically discussing with parents what information would be in their child's interests to hear. To ensure ongoing parental access to separate consultations, consideration should be given to ways of facilitating these, including shifting the onus for initiating separate consultations from parents to doctors.